NEXUS OF TREASURY SINGLE ACCOUNT AND FINANCIAL ACCOUNTABILITY IN OYO STATE, NIGERIA - Muhammed Basiru MUSTAPHA (Malete Journal of Accounting and Finance, 2022)
The establishment of Treasury Single Account reduced proliferation of accounts of ministries, departments and agencies which in turn encouraged financial accountability among government organs in Oyo state.  It is on this note that this study investigated how treasury single account aided financial accountability in the public sector of Oyo state. This was achieved using survey research design and the study population was made up of sampled staff of MDAs in Oyo state. Primary data was collected through the administration of questionnaires. The result of the hypotheses tested showed that three out of the four formulated hypotheses were significantly related to financial accountability except for unification of government revenue that has no significant effect. Thus, indicating that treasury single account goes a long way in aiding financial accountability. This study thus recommends that operational challenges, financial control and operational efficiency are key predictors of financial accountability in the public sector of Oyo state.